THE POOR IN THOMAS GRAY'S ELEGY WRITTEN IN A COUNTRY CHURCHYARD: CRITICAL DISCOURSE ANALYSIS APPROACH - Hidayati Hidayati; Zuindra Zuindra; Mayasari Mayasari; Misla Geubrina; Arifuddin Arifuddin (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2018)
The research deals with the problems of poverty with the aim of revealing the situation of rural people experiencing various   shortages throughout their daily needs. This poem is also a personal picture of the poet seeing by firsthand the situation of the marginalized people. Through critical discourse analysis by means of Van Dijk model consisting of three dimensions, namely text, social cognition and social context, the picture of the poor in the poem can be seen clearly. The data used are lines of Stanza No. 13 as a representation of the whole poem. The method used is descriptive qualitative. The results of the research indicate that knowledge or education is not limited to one group, but for all; but in practice the poor do not always get the opportunity to obtain proper education. The voice of the poor is not heard; therefore, they are bound by circumstances and cannot do much. In connection with critical discourse analysis, at the level of text, the general theme is the death and fate of the people on the periphery of the society. In the data related, the theme is the absence of opportunities for the poor to get education; the storyline starts from the causes and consequences of poverty and in the microstructure level there are syntactic and lexicon elements. The level of social cognition describes the close relationship between the poet and the elegy and of social conditions pictures the historical background of the text production.